Lucas, Peter J. 2024. Old English Poetry from Manuscript to Message. Utrecht Studies in Medieval Literacy 58. Turnhout: Brepols. Pp. xviii + 398. ISBN 9782503600314. - Mark Griffith (SELIM)
Book review of Lucas, Peter J. 2024. Old English Poetry from Manuscript to Message. Utrecht Studies in Medieval Literacy 58. Turnhout: Brepols. Pp. xviii + 398. ISBN 9782503600314.